The Effect of Direct Expenditure on Education and Health on Human Development Index in Mataram City in 2013-2022 - Micko Yusuf Setiawan; Muaidy Yasin; Siti Sriningsih; Marashdeh , Hazem A. (Journal of Social and Humanities, 2024)
This study aims to analyze the effect of direct spending in the education and health sectors on the human development index in Mataram City in 2013-2022. This type of research is Quantitative research. The results showed that the partial test results of direct expenditure in the health sector did not have a significant effect on the human development index in Mataram City as seen from the significance value above 0.05. And partially the influence of direct expenditure budget in the field of education has a significant influence on the human development index in Mataram City, which is seen from the significance value below 0.05. Simultaneous test results show that the effect of direct expenditure in the education and health sectors together has a significant effect on the human development index, which is seen from the significance value below 0.05.